Development of assessment for learning-oriented electronic student worksheets to improve student learning outcomes on acid-base titration material - Afiqa Azra Amanina; Muchlis Muchlis (Jurnal Pijar Mipa, 2023)
This study aims to describe the feasibility of an Electronic Student Worksheet-oriented assessment for learning to improve the learning outcomes of class XI students of SMAN 1 Menganti Gresik, Indonesia, on acid-base titration material. The feasibility of the Electronic Student Worksheet developed is reviewed based on three aspects: validity, practicality, and effectiveness. This study used a Research and Development (R&D) method development design that refers to the Borg and Gall research and development model. This research was limited to the limited trial stage. The little trial was conducted on 18 SMAN 1 Menganti Gresik students who had received acid-base titration material. The feasibility of the Electronic Student Worksheet was reviewed from the validity aspect obtained based on the assessment results by the validator, which consisted of two chemistry lecturers from FMIPA Surabaya State University and one chemistry teacher from SMAN 1 Menganti Gresik. Validation by experts related to content validity and construct validity obtained a mode of 5 with a highly valid category. Practicality in students' responses by getting a positive reaction of 97.22% with a very practical category and observation of students' activities as supporting data which obtained more excellent students' relevant activities with an average percentage at the first meeting and the second meeting of 95%. Effectiveness in terms of the results of students' cognitive learning tests which have increased with the percentage of students who get N-gain in high criteria by 11%, while the percentage of students who get N-gain in medium criteria is 83%, and the percentage of students who get N-gain in low criteria is 6%. In the second meeting, the rate of students who got N-gain in high criteria increased by 89%, while the percentage of students who got N-gain in moderate criteria was 11%.